Spectrophotometric Determination of Promethazine Hydrochloride and Paracetamol in Pharmaceutical Tablets - Al-Saidi, Khaleda H; Hammza, Rana A (Al-Nahrain Journal of Science, 2018)
Spectrophotometric techniques were developed for the determination of single and binarymixture Promethazine hydrochloride (PMH) and Paracetamol (PCM). Normal and first derivative (1D) used for single drug at λ 249.5 and 243.0 for PMH and 243.5 and 225 for PCM. The simultaneous determination of binary mixture (PMH) and (PCM) were accomplished by first derivative (1D) and second derivative (2D) spectrophotometric technique with applying zero-crossingat valley (V=216.5) and Peak (P=258.8)nm for (PMH) and (V=274.0 and P=299.2 nm for PCM).The correlation coefficient for calibration curves not less than 0.999 and the relative standard deviation not exceed to 0.214. The recovery of individual constituents under establishedconditions inthe ranges from 97.00% to 101.97 %. Linearity is maintained within a wide concentrationrange from 4.00-30.00mg/L for PMH and PCM. Standard addition method used forpharmaceutical tablets. A good accuracy and precision of simultaneous determination of (PCM), and (PMH) were confirmed by statistical analysis. The proposed procedures were successfully applied to the determination of these compounds in different ratio by synthetic mixtures and pharmaceutical tablets without requiring any separation step.